Vaginectomy in Transmasculine Patients: A Review of Techniques in an Emerging Field. Issue 6 (17th June 2022) - Coulter, Madeline; Diamond, David A.; Estrada, Carlos; Grimstad, Frances; Yu, Richard; Doyle, Paula
Abstract : Purpose: This report reviews the various techniques for vaginal obliterative surgery in the transmasculine patient population, including advantages and drawbacks with differing methods and reflects on the focus of future research and surgical efforts. Findings: Existing techniques for vaginal obliterative surgery by vaginectomy or colpocleisis vary without strong evidence to identify a superior approach. Summary: The increasing number of transmasculine patients seeking vaginectomy as a part of gender-affirming surgery must be matched by evidence-based techniques that provide a safe, long-term outcome.